Primary results of the randomized trial of metformin administration in polycystic kidney disease (TAME PKD) - Perrone, Ronald D; Abebe, Kaleab Z; Watnick, Terry J; Althouse, Andrew D; Hallows, Kenneth R; Lalama, Christina M; Miskulin, Dana C; Seliger, Stephen L; Tao, Cheng; Harris, Peter C; Bae, Kyongtae Ty (Kidney international, 2021)
Autosomal dominant polycystic kidney disease (ADPKD) is characterized by growth of kidney cysts and glomerular filtration rate (GFR) decline. Metformin was found to impact cystogenesis in preclinical models of polycystic disease, is generally considered safe and may be a promising candidate for clinical investigation in ADPKD. In this phase 2 two-year trial, we randomly assigned 97 patients, 18-60 years of age, with ADPKD and estimated GFR over 50 ml/min/1.73 m , in a 1:1 ratio to receive metformin or placebo twice daily. Primary outcomes were medication safety and tolerability. Secondary outcomes included estimated GFR decline, and total kidney volume growth. Thirty-eight metformin and 39 placebo participants still received study product at 24-months. Twenty-one participants in the metformin arm reduced drug dose due to inability to tolerate, compared with 14 in the placebo arm (not significant). Proportions of participants experiencing serious adverse events was similar between the groups. The Gastrointestinal Symptoms Rating Scale score was low at baseline and did not significantly change over time. The annual change for estimated GFR was -1.71 with metformin and -3.07 ml/min/1.73m per year with placebo (mean difference 1.37 {-0.70, 3.44} ml/min/1.73m ), while mean annual percent change in height-adjusted total kidney volume was 3.87% in metformin and 2.16% per year in placebo, (mean difference 1.68% {-2.11, 5.62}). Thus, metformin in adults with ADPKD was found to be safe and tolerable while slightly reducing estimated GFR decline but not to a significant degree. Hence, evaluation of efficacy requires a larger trial, with sufficient power to detect differences in endpoints.